Internalisasi Nilai Pancasila sebagai Upaya Harmonisasi Beragama di Indonesia - Mohammad Firmansyah; Rahwan; Redite Kurniawan; Mohamad Salik (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
Numerous acts of terrorism in Indonesia highlight the insufficient understanding and appreciation of moderation values. To combat terrorism and radicalism, a multifaceted approach is essential. This study examines the effectiveness of a deradicalization program that integrates Pancasila education and promotes moderate values through religious moderation education. The research posits that moderate Islamic education can prevent students from adopting radical behaviors and thoughts. Consequently, the graduates of Islamic educational institutions are better equipped to embrace religious diversity and respect differing beliefs. This qualitative study employs contextual and textual analysis of relevant articles to explore this topic. The findings reveal that the internalization of Pancasila values involves a three-step process: transformation, transaction, and internalization. These steps are crucial for harmonizing religious understanding and promoting tolerance. This study underscores the importance of embedding Pancasila values in educational curricula to foster a more moderate and inclusive society